Diseño arquitectónico del Campo Santo – sector los Llanos del cantón Pallatanga, provincia de Chimborazo - Zavala López, Frank Alexis (2019)
Cemeteries in Ecuador are increasingly necessary, because the population grows every day consequently the death toll is spread and these places are the focus of many problems. This project is focused on providing an architectural proposal for the Pallatanga canton, Los Llanos area, Chimborazo province, which has the purpose of implementing a service to the community through the design of a Municipal Holy Field, Since the present day cemetery is obsolete, through previous study carried out by the GADMP, which was built in 1964, for this reason it is necessary to create a new urban equipment for the city of Pallatanga such as the Municipal Holy Field, which has adequate and modern facilities, new burial system, burial, cremation , mausoleums and green areas in order to integrate the city, the area and the urban landscape. The present day cemetery shows problems, both in its infrastructure, as in its organization, maintenance of vaults and tombs because in the moment of its construction, there was not an adequate study of the land, since it is fully occupied, burials are carried out on occupied plots of land. The diagnosis allowed to define the real demand for the service to be captured, in which 57% remarks that the current cemetery is deteriorated, 98% do not provide the necessary security, 84% do not know the funeral services offered by the current cemetery, 82% agree on the construction of a new holy field, 100% would like to acquire a property in the new cemetery an finally 91% would like to acquire economic packages about the services to be offered in the new holy field. Using urban analysis, site analysis, and architectural ant theoretical references as a model for the development of the project, strategies for responding to social, urban and technical conditions were identified